Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1017/s0950268816002387
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and microbiological characterization of clinical isolates of Staphylococcus aureus in a single healthcare region of the UK, 2015

Abstract: We investigated the epidemiology and characterization of isolates of Staphylococcus aureus within the Yorkshire and Humber (YH) region in the UK. In July 2015, each laboratory within YH (n = 14) was assigned two consecutive days during which all clinical isolates of S. aureus were collected. Isolates were tested for antibiotic susceptibilities and the presence of genes encoding methicillin resistance (mecA and mecC), Panton-Valentine leukocidin (PVL) (lukS-PV), and efflux-mediated chlorhexidine resistance (qac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Since then, several retrospective and prospective studies using human S. aureus isolates/samples were carried out in order to search for mecC -MRSA isolates ( Table 1 and Table 2 ) [ 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several retrospective and prospective studies using human S. aureus isolates/samples were carried out in order to search for mecC -MRSA isolates ( Table 1 and Table 2 ) [ 16 , 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ,…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…In any case, the mecC -MRSA human prevalence detected in most of the studies was very low. Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ].…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…The number of isolates needed to determine the prevalence of mecC in our S. aureus population was calculated using the equation described by Jones et al, using a 95% confidence level, a 5% precision level, and an expected proportion of 6.2% based on the recently reported mecA prevalence (10,12). Based on this equation, at least 89 isolates would need to be tested.…”
mentioning
confidence: 99%
“…It is against this backdrop that we note the recent results of a screening program in Yorkshire and the Humber Region of the UK (19). In total, 520 isolates of S. aureus were identified from clinical samples, and the prevalence of mupirocin resistance was low at 0.8%.…”
Section: Discussionmentioning
confidence: 90%